2001
DOI: 10.1021/ja0023581
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolyses of Chlorodifluoromethane and Trifluoromethane in the Presence of Hydrogen. Mechanism and Optimization of Reaction Conditions

Abstract: When CHClF 2 and CHF 3 are subjected to high-temperature, gas-phase flow pyrolysis in the presence of H 2 , they are converted, via a free radical chain mechanism, to CH 2 F 2 , CHF 2 CHF 2 , and CF 3 CH 2 F in good yield. Optimal conditions for pyrolysis of CHClF 2 involve a high conversion (92%) at 650 °C with an observed yield of products ) 18, 17, and 28%, respectively, whereas optimal conditions for CHF 3 involve a low conversion (24%) at 775 °C, but a higher yield of products (26, 6, and 39%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Relative molar response (RMR) factors of fluorocarbons for TCD detection were experimentally obtained from standard gas mixtures, and quantification of halogenated hydrocarbons was performed with diluted halogenated hydrocarbons in nitrogen. Quantification of other species was estimated from published correlations [8][9][10].…”
Section: Catalytic Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative molar response (RMR) factors of fluorocarbons for TCD detection were experimentally obtained from standard gas mixtures, and quantification of halogenated hydrocarbons was performed with diluted halogenated hydrocarbons in nitrogen. Quantification of other species was estimated from published correlations [8][9][10].…”
Section: Catalytic Experimentsmentioning
confidence: 99%
“…Consensus exists in the literature that the initial step of homogeneous gas phase pyrolysis of CHF 3 is the elimination of HF at temperatures above 1023 K leading to formation of CF 2 , which rapidly dimerises to C 2 F 4 which is the major product of the reaction [10,11].…”
Section: Decomposition Of Chf 3 Over Activated Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that pyrolysis of CHF 3 at high temperature leads to the formation of tetrafluoroethene (TFE) as the major product, and the mechanism of this process involves the dehydrofluorination of CHF 3 to form difluorocarbene, which then dimerizes to form TFE [16][17][18].…”
Section: Pyrolysis Of Trifluoromethane On Activated Charcoalmentioning
confidence: 99%
“…Raphaele et al obtained CH 2 F 2 by reacting H 2 with CHF 3 at the temperature of 775 8C, and proposed the mechanism involved CF 2 carbene intermediate [16]. Wheaton and Burton used 2-methyl-2-butene, a electron-rich alkenes, to trap CF 2 carbene intermediate at the temperature of 120 8C and obtained gem-difluoro-2,2,3-trimethylcyclopropane to confirm the CF 2 carbene intermediate [19].…”
Section: Pyrolysis Of Trifluoromethane On Activated Charcoalmentioning
confidence: 99%